Historical Corpora - Gippert, Jost,Gehrke, Ralf (Narr Francke Attempto Verlag, 2015)
The volume contains 23 papers read at the international conference
9783823379225
Keywords: Historical corpora; Diachronic corpora; Digital Humanities; Corpus linguistics